ACHIZIŢIA, PRELUCRAREA ŞI GESTIONAREA DATELOR SPAŢIALE ÎN CONTEXTUL CERCETĂRĂRILOR ARHEOLOGICE EFECTUATE ÎN CADRUL STAŢIUNII PUŢUL TĂTARULUI, JUD. PRAHOVA (PANGEEA, 2025)
This paper aims to channel some ideas on an unique path of topographical inventory data of archaeological site through designing and managing a computerized database corresponding to some pilotarchaeological site (Puţul Tătarului), useful and applicable nationwide, out of which the topo-archaeological information may result quickly and securely, according to the research objectives.